Hubungan Status Gizi dengan Prestasi Belajar Siswa SD Katolik St Fransiskus Xaverius Kakaskasen Kota Tomohon - Rawung, Meilita M.; Wungouw, Herlina I. S.; Pangemanan, Damajanty H. C. (Universitas Sam Ratulangi, 2020)
Abstract: School-age children are in an active period of growth and development. Good nutritional status will lead to optimal health degree and improve the thinking ability and learning performance of school-age children. This study was aimed to determine the relationship between nutritional status and students’ learning achievement in elementary school. This was a descriptive and analytical study with a cross sectional design. There were 109 elementary school students who fulfilled the inclusion and exclusion criteria. Nutritional status was measured with anthropometric index based on body mass index according to child’s age (BMI-for-age). Learning achievement was based on the value of midterm exams. Based on BMI-for-age index, it was found that most children had normal nutritional status (68.8%), 6 children had underweight nutritional status (5.5%), 14 children had overweight nutritional status (12.8%), and 14 children with obese nutritional status (12.8%). The Fisher's Exact test analyzing the relationship between nutritional status and learning achievement showed a p-value of 0.951 (p>0.05). In conclusion, there was no relationship between nutritional status and learning achievement among students of St. Fransiskus Xaverius Kakaskasen Catholic Elementary School in Tomohon.Keywords: nutritional status, learning achievement, elementary school students Abstrak: Anak usia sekolah merupakan kelompok anak yang berada pada masa aktif dalam pertumbuhan dan perkembangan. Status gizi yang baik akan berdampak derajat kesehatan yang optimal dan membantu anak sekolah dalam meningkatkan kemampuan daya pikir dan performa belajar. Penelitian ini bertujuan untuk mengetahui hubungan antara status gizi dengan prestasi belajar pada siswa sekolah dasar. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang dilakukan pada 109 siswa sekolah dasar yang memenuhi kriteria inklusi dan eksklusi. Status gizi dinilai menggunakan indeks antropometri berdasarkan indeks massa tubuh menurut umur anak (IMT/U). Prestasi belajar diukur berdasarkan nilai ujian tengah semester. Hasil penelitian mendapatkan bahwa berdasarkan indeks IMT/U, sebagian besar anak memiliki status gizi normal (68,8%), 6 anak memiliki status gizi kurang, 14 anak dengan status gizi lebih (12,8%), dan 14 anak dengan status gizi obes (12,8%). Hasil uji Fisher’s Exact terhadap hubungan antara status giz dan prestaasi belajar menunjukkan nilai p=0,951 (p>0,05). Simpulan penelitian ini ialah tidak terdapat hubungan antara status gizi dengan prestasi belajar siswa SD Katolik St. Fransiskus Xaverius Kakaskasen Kota Tomohon.Kata kunci: status gizi, prestasi belajar, siswa sekolah dasar